2007
DOI: 10.1111/j.1460-9568.2007.05560.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress‐mediated increases in extracellular glutamate levels in the rat amygdala: differential effects of antidepressant treatment

Abstract: Depressive illness is associated with changes in amygdalar volume, and stressful life events are known to precipitate depressive episodes in this patient population. Stress affects amygdalar synaptic plasticity and several neurotransmitter systems have been implicated in stress-mediated changes in the brain, including the glutamatergic system. However, the role of the glutamatergic system in stress-mediated plasticity in the amygdala remains to be determined. Accordingly the current study examined the stress m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 51 publications
6
115
1
2
Order By: Relevance
“…In addition, membrane depolarization is essential for contraction of skeletal muscle (Liu et al 2009), suggesting that increased muscle tension during stress may be the result of widespread depolarization. During stress, the release of the excitatory neurotransmitter glutamate in the amygdala (Reznikov et al 2007), and prefrontal cortex is mediated by depolarization (Musazzi et al 2010). Stress and depression are also associated with increased amygdala activity and chronic stress leads to neuronal hyperactivity in the amygdala, suggesting that a reduction in this excitatory drive may be a potential treatment (Padival et al 2013).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%
“…In addition, membrane depolarization is essential for contraction of skeletal muscle (Liu et al 2009), suggesting that increased muscle tension during stress may be the result of widespread depolarization. During stress, the release of the excitatory neurotransmitter glutamate in the amygdala (Reznikov et al 2007), and prefrontal cortex is mediated by depolarization (Musazzi et al 2010). Stress and depression are also associated with increased amygdala activity and chronic stress leads to neuronal hyperactivity in the amygdala, suggesting that a reduction in this excitatory drive may be a potential treatment (Padival et al 2013).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%
“…Tianeptine-induced decrease in NMDA-EPSCs reported here suggests a similar mechanism in the amygdala. Further, Reznikov et al (2007) have shown that extracellular glutamate levels are enhanced by stress in the amygdala, and this too is reversed by tianeptine. Thus, excess glutamate and its electrophysiological actions on receptors that trigger plasticity are both targeted by tianeptine in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…The atypical antidepressant tianeptine is reported to be remarkably effective in preventing many of these stress effects on structural and physiological markers of plasticity, including those involving glutamatergic transmission (Kole et al, 2002;Qi et al, 2009;Reagan et al, 2004;Reznikov et al, 2007;Vouimba et al, 2006;Watanabe et al, 1992). Therefore, we first investigated the effects of tianeptine on EPSCs mediated by a-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors (AMPARs) and N-methyl-D-aspartate receptors (NMDARs).…”
Section: Tianeptine Potentiates Synaptic Currents Mediated By Ampa Anmentioning
confidence: 99%
“…Depression impairs cognition through stress-induced alterations in the morphology and metabolism of the hippocampus in the brain. 19,20 Regression, which is a retreat from an achieved level of mature adaptation, is a major threat to the injured worker's recovery. Regression commonly occurs in frightened people who do not have a strong support system.…”
Section: Risk Of Compromised Medical Outcomementioning
confidence: 99%